Impact of cocaine abuse on HIV pathogenesis - Dash, Sabyasachi; Balasubramaniam, Muthukumar; Villalta, Fernando; Dash, Chandravanu; Pandhare, Jui (Frontiers in Microbiology, 2015)
Over 1.2 million people in the United States are infected with the human immunodeficiency virus type 1 (HIV-1). Tremendous progress has been made over the past three decades on many fronts in the prevention and treatment of HIV-1 disease. However, HIV-1 infection is incurable and antiretroviral drugs continue to remain the only effective treatment option for HIV infected patients. Unfortunately, only three out of ten HIV-1 infected individuals in the US have the virus under control. Thus, majority of HIV-1 infected individuals in the US are either unaware of their infection status or not connected/retained to care or are non-adherent to antiretroviral therapy (ART). This national public health crisis, as well as the ongoing global HIV/AIDS pandemic, is further exacerbated by substance abuse, which serves as a powerful cofactor at every stage of HIV/AIDS including transmission, diagnosis, pathogenesis, and treatment. Clinical studies indicate that substance abuse may increase viral load, accelerate disease progression and worsen AIDS-related mortality even among ART-adherent patients. However, confirming a direct causal link between substance abuse and HIV/AIDS in human patients remains a highly challenging endeavor. In this review we will discuss the recent and past developments in clinical and basic science research on the effects of cocaine abuse on HIV-1 pathogenesis.